Improving the Capability of Cow HID Processing Entrepreneurs in the Use of Technology to Expand the Export Market (Case Study: Garut District Cow Processing MSMEs) - Maisa Azizah Asmara; Hamidah Hamidah; Anita Luthfiyati; Wahyu Nurjaya WK; Wulan Siti Rodiah (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
The potential to improve the Indonesian economy can be achieved through the development of micro, small, and medium enterprises (MSMEs), one of which is the cowhide MSME in Garut Regency (Vernanda et al., 2023). The need to improve the capacity of cowhide entrepreneurs is great, but the use of technology is not optimal for expanding the market (Solihah & Zakiah, 2022). The objective of this community service is to strengthen the capacity of cowhide MSMEs to use technology to expand export markets. This is accomplished through training, mentoring, and consulting that addresses the use of technology related to product marketing, content creation, financial reporting, and markets. The expected outcome of the community service is to enhance the skills of Garut Regency tanneries in using digital technology to market products with interactive product designs and appropriate financial reporting. by accounting standards and market management.